2020
DOI: 10.1111/anu.13184
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, robustness against stress, serum insulin, IGF‐1 and GLUT4 gene expression of red tilapia (Oreochromis sp.) fed diet containing graded levels of creatine

Abstract: The experimental diets containing five levels of creatine supplementation, namely control (N = 0 g/kg creatine), B1 (1.00 g/kg glycine), B2 (0.40 g/kg creatine), B3 (0.80 g/kg creatine) and B4 (1.20 g/kg creatine) were tested to red tilapia up to apparent satiation 3 times a day for 56 days. After the feeding trial, fish were stressed by air exposure for challenge test against stress. The results described that creatine supplementation improved final body weight, feed conversion ratio (FCR) and protein retenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 52 publications
4
27
0
Order By: Relevance
“…The oxidative protein deamination will accelerate the excretion rate of ammonia to the aquatic environment, which may accumulate within the system and harm the fish itself (Lazzari & Baldisserotto, 2008). Synergistic of cysteamine as an insulin stimulator through suppressing somatostatin production (Wardani et al, 2020a; Xiao & Lin, 2003) and creatine as an energy buffer ready to use (Borchel et al, 2014; Wardani et al, 2020b) in fish.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The oxidative protein deamination will accelerate the excretion rate of ammonia to the aquatic environment, which may accumulate within the system and harm the fish itself (Lazzari & Baldisserotto, 2008). Synergistic of cysteamine as an insulin stimulator through suppressing somatostatin production (Wardani et al, 2020a; Xiao & Lin, 2003) and creatine as an energy buffer ready to use (Borchel et al, 2014; Wardani et al, 2020b) in fish.…”
Section: Discussionmentioning
confidence: 99%
“…The lower liver glycogen (Table 2) and muscle glycogen values (Table 2) ( p < 0.05) in treatment C compared to controls, reinforced the increase in protein sparing effect so that oxidative deamination was reduced (Subramanian, 2013; Wardani et al, 2020a). Reduced oxidative deamination would cause a decrease in the value of reactive oxygen species (ROS) (Andersen et al, 2016), free radicals (Lupatsch et al, 2010; Zupa et al, 2015), MDA (Abdel‐Daim et al, 2020; Wardani et al, 2020a, 2020b) and plasma cortisol (Schrama et al, 2018) as stress indicators. In this study, fish fed with treatment C showed lower MDA (Table 2), cortisol and glucose values ( p < 0.05), respectively, at 30.26%, 7.57% and 15.89% compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations